„Paciorki mozaikowe w otwartym palenisku?”. Kontynuacja badań - Krzyżanowska, Marta; Frankiewicz, Mateusz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
The aim of the experiment was to confirm the hypothesis about the possibility of Scandinavian bead makers crafting complex mosaic glass beads. For this purpose, raw glass material and tools from archaeological sites were examined. Metal tools and glass mosaic canes were made, for the purpose of the experiment, based on archaeological finds. All the glass beads were made during the experiment on a specially constructed open hearth. As a result of the experiments, the possibility of making mosaic glass beads on an open hearth was confirmed. A theoretical and practical procedure for making complex glass beads has been proposed.